INCREASING THE STUDENTS’ ABILITY IN READING COMPREHENSION BY USING GIVE ONE GET ONE STRATEGY AT THE EIGHTH GRADE OF SMP NEGERI 3 MANDREHE 2020/2021 - Adieli Laoli; Elwin Piarawan Zebua (TEHUDE: Jurnal Ilmiah Pendidikan Bahasa Inggris, 2022)
Reading activity has one of the ways to catch up information, to know enough science concepts, to know more knowledge, to understand scientific books and technology written in the English language. Through reading the reader may have satisfaction and comfort. Factually, the eighth grade students of SMP Negeri 3 Mandrehe were unable to comprehend a descriptive text fully, lack vocabulary, unable to determine the main idea and the students were unable to identify the features and generic structure. To overcome the problems, Give One Get One Strategy was implemented to increase the students’ ability in reading comprehension descriptive text. The research method was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of two meetings. The result of the data in Cycle I that there were 3 students (15%) in fail level, 12 students (60%) less level, 2 students (10%) in the enough level, 3 students (15%) in the good level, and 0 student in the very good level. The average of the students’ value was 52.5. This result showed that the students were unsuccessful. In Cycle II that there were 12 students (60 %) in the enough level, 6 students (30%) in the good level, and 2 students (10%) in the very good level. The average of the students’ value is 74.5. The result showed that the students’ reading comprehension was increased